The Applicability of Graduate Studies in Employment in Labour Market - Chathurika Weerasekara, M. (University of Jaffna, 2014)
Relevant knowledge and necessary skills are considered as pre requirements for good labor market outcomes. One of the most important ideas in labor economics is to think of the set of marketable skills of employees as a form of capital in which they make a variety of investments. This paper was an attempt to move forward on this situation. The primary objective of this study was to determine the degree of applicability of occupied employees’ graduate studies in labor market and to identify the consequences of the situation. The study was conducted among employees in private and public sector who have been passed out from state universities in Sri Lanka. Random sampling method was used to select the sample and a total of 100 questionnaires were provided for the actual survey. Only 75 questionnaires were taken to the consideration which was a 91.4 per cent of response rate. Two main research instruments were used in the study; questionnaires and interviews. Descriptive statistics were used to organize, summarize and describe the collected data. In addition Cronbach’s Alpha was used for assessing the reliability of the questionnaire scored with a Likert-type scale. A concise conclusion of findings revealed that, due to the lack of job opportunities in the most applicable field, low job interest, low attractiveness of remuneration and allowances, lack of opportunities to upgrade in career path, internal domination in requirements and promotions, graduates tempt to change their employment when they enter/ after they entered to the job market. And also for the employees who are working in irrelevant areas which are not directly applicable with their graduate study job objectives, have faced a massive problem with the time and money they had spent on.
Keywords: Graduate education; Employees